The effect of two β-alanine dosing strategies on 30-minute rowing performance: a randomized, controlled trial. Issue 1 (18th December 2018) - Beasley, Liam; Smith, Lee; Antonio, Jose; Gordon, Dan; Johnstone, James; Roberts, Justin
Abstract: Background: β-alanine (βA) supplementation has been shown to increase intramuscular carnosine content and subsequent high-intensity performance in events lasting < 4 minutes (min), which may be dependent on total, as opposed to daily, dose. The ergogenic effect of βA has also been demonstrated for 2000-m rowing performance prompting interest in whether βA may be beneficial for sustained aerobic exercise. This study therefore investigated the effect of two βA dosing strategies on 30-min rowing and subsequent sprint performance. Methods: Following University Ethics approval, twenty-seven healthy, male rowers (age: 24 ± 2 years; body-height: 1.81 ± 0.02 m; body-mass: 82.3 ± 2.5 kg; body-fat: 14.2 ± 1.0%) were randomised in a double-blind manner to 4 weeks of: i) βA (2.4 g·d − 1, βA1); ii) matched total βA (4.8 g on alternate days, βA2); or iii) cornflour placebo (2.4 g·d − 1, PL). Participants completed a laboratory 30-min rowing time-trial, followed by 3x30-seconds (s) maximal sprint efforts at days 0, 14 and 28 (T1-T3). Total distance (m), average power (W), relative average power (W·kg − 1 ), cardio-respiratory measures and perceived exertion were assessed for each 10-min split. Blood lactate ([La-]b mmol·L − 1 ) was monitored pre-post time-trial and following maximal sprint efforts. A 3-way repeated measures ANOVA was employed for main analyses, with Bonferonni post-hoc assessment ( P  ≤ 0.05). Results: Total 30-min time-trial distance significantly increased from T1-T3 within βA1 only (7397 ± 195 m to 7580 ± 171 m, P  = 0.002, ƞp 2  = 0.196), including absolute average power (194.8 ± 18.3 W to 204.2 ± 15.5 W, P  = 0.04, ƞp 2  = 0.115) and relative average power output (2.28 ± 0.15 W·kg − 1 to 2.41 ± 0.12 W·kg − 1, P  = 0.031, ƞp 2  = 0.122). These findings were potentially explained by within-group significance for the same variables for the first 10 min split ( P  ≤ 0.01), and for distance covered ( P  = 0.01) in the second 10-min split. However, no condition x time interactions were observed. No significant effects were found for sprint variables ( P  > 0.05) with comparable values at T3 for mean distance (βA1: 163.9 ± 3.8 m; βA2: 161.2 ± 3.5 m; PL: 162.7 ± 3.6 m), average power (βA1: 352.7 ± 14.5 W; βA2: 342.2 ± 13.5 W; PL: 348.2 ± 13.9 W) and lactate (βA1: 10.0 ± 0.9 mmol·L − 1 ; βA2: 9.2 ± 1.1 mmol·L − 1 ; PL: 8.7 ± 0.9 mmol·L − 1 ). Conclusions: Whilst daily βA may confer individual benefits, these results demonstrate limited impact of βA (irrespective of dosing strategy) on 30-min rowing or subsequent sprint performance. Further investigation of βA dosage > 2.4 g·d − 1 and/or chronic intervention periods (> 4–8 weeks) may be warranted based on within-group observations.